Cancel culture як інструмент впливу у політичній боротьбі - Molochko, Pavlo; Hryniova, Daria (Чернівецький національний університет імені Юрія Федьковича, 2022)
Останніми роками феномен cancel culture набуває все більшої популярності як в соціальних мережах, так і в реальному житті. Розглядаючи становлення цього феномену, автори статті, аналізують його виникнення та поширення у суспільстві. Автори звертають увагу на те, що феномен культури скасування виникав як засіб привертання уваги до дій окремих політиків, які були вчинені раніше, але є неприйнятними у сучасному суспільстві. Поступово цей феномен з інструменту осуду у соціальних мережах поширюється і на використання у політичній боротьбі. Аналізуючи кейси політизації феномену культури скасування у США, Канаді та Україні, автори приходять до висновку, що спільною рисою для всіх країн є намагання переосмислити історичні події крізь призму феномену cancel culture. Ставлення до cancel culture у сучасних суспільствах не є однозначним. Наслідком цього є поява прихильників та критиків цього феномену. Поширення cancel culture на політичну боротьбу несе певні ризики, що пов’язані з необхідністю надмірного контролю за свободою думки та слова. In recent years, the phenomenon of cancel culture has been gaining traction on social media as well as in real life. Considering the formation of this phenomenon, the authors of the article analyse its emergence and the way it spreads in society. The authors of the article emphasise the fact that cancel culture arose as a means of drawing attention to the actions of individual politicians, committed earlier, but unacceptable in modern society. Gradually, cancel culture has extended from the tool of condemnation on social media to its use in political struggle. The authors of the article analyse cases of politicization of cancel culture in the USA, Canada and Ukraine. Based on the analysis, the authors come to the conclusion that a common feature for all countries is the attempt to reconsider historical events through the lens of cancellation. The attitude towards cancel culture in modern societies is rather ambi-guous. The consequence of this is the appearance of supporters and critics of this phenomenon. Extending cancel culture to the political struggle carries certain risks associated with the need for excessive control over freedom of thought and speech. ‘Cancellation’ is used not only as a tool for manifesting a position on social media, but also becomes a tool in manipulative campaigns and information wars. Meanwhile, conducted studies show that the very appearance of such a phenomenon leads to the fact that representatives of certain groups are not ready to defend their views, if such views are not widely shared by society. That is why the phenomenon of cancel culture needs further detailed study and understanding.
Cancel Culture: Leverage Tool in Political Struggle
Keywords: cancel culture; культура скасування; політична боротьба; вплив; суспільство; political struggle; influence; society